If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -9x = 182 + -44x Solving 12 + -9x = 182 + -44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44x' to each side of the equation. 12 + -9x + 44x = 182 + -44x + 44x Combine like terms: -9x + 44x = 35x 12 + 35x = 182 + -44x + 44x Combine like terms: -44x + 44x = 0 12 + 35x = 182 + 0 12 + 35x = 182 Add '-12' to each side of the equation. 12 + -12 + 35x = 182 + -12 Combine like terms: 12 + -12 = 0 0 + 35x = 182 + -12 35x = 182 + -12 Combine like terms: 182 + -12 = 170 35x = 170 Divide each side by '35'. x = 4.857142857 Simplifying x = 4.857142857
| 0.07x-0.04=-0.18 | | x=9.5 | | 5x/4y=0 | | -125-7x=1 | | -0.4x-0.08y=4 | | .15(2x-5)=3 | | 2t=108 | | 13-8x=40-15 | | 0.07x/0.08y=0.77 | | 13-8x=10x-15 | | 13-8x=10x+15 | | 0.2x-0.05y=0.29 | | 0.7x/0.4y=0.2 | | 0.2x/0.3y=1.1 | | x^3+7x^2-22x-10=0 | | a+2(a+1)=8 | | 3/4x+3/5y=3/4 | | 4x-56=98 | | 9(x-2)=8(x-1) | | 3x+114=7x-6 | | 5n/n+3=n-8 | | 12-9x=99-37x | | 4(x-3)-3(x-1)=2(x-1)-3(x+1) | | 4t=240 | | 3n-35=79 | | 3r=81 | | 8(x-9)=3(x-4) | | 16-2x=19-4x | | 9d=72 | | f(x)=2x^2+9x-1 | | 9/x+3=0 | | f(x)=81 |